Az euró bevezetésének lehetséges előnyei és hátrányai, az euró szerepe Sopron városában - Szőke Judit (2019)
Sopron’s close proximity to Austria and its symbiosis with the Austrian economy justifies the assumption that the introduction of the Euro in Hungary would have a different effect on Sopron than on the other parts of the country. The initial hypothesis is that the use of Euro is already so deeply engrained in the city’s economy that a Hungarian euro introduction would have no real impact in Sopron. At first I outlined the background of the problem: pro primo the history of the Euro, the way to its formation, pro secundo the current situation in Hungary regarding the introduction and its possible effects on a macro- and microeconomic scale, pro tertio the special economic and geographic characteristic of Sopron and its use of the Euro. To examine the prevalence of euro in Sopron’s economy I have chosen the method of comparing its data to that of Eger – a city of comparable population, tourism and industry.